2015
DOI: 10.4103/0253-7184.167160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiretroviral therapy on mucocutaneous manifestations among Human Immunodeficiency Virus-infected patients in a tertiary care centre in South India

Abstract: Background:Human Immunodeficiency Virus (HIV) infection produces a wide range of infectious and noninfectious dermatoses which correlate with the degree of immunodeficiency. Since the introduction of highly active antiretroviral therapy (HAART), there has been a dramatic decrease in the incidence of HIV-associated dermatoses. However, HAART itself causes various cutaneous adverse drug reactions.Aims:To assess the various mucocutaneous manifestations in HIV-infected individuals and its association with CD4 coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In a study starting antiretroviral drugs in HIV-positive patients led to many skin reactions. [ 18 ] In this study, 26 patients (10.8%) had a history of drug reaction.…”
Section: Discussionmentioning
confidence: 88%
“…In a study starting antiretroviral drugs in HIV-positive patients led to many skin reactions. [ 18 ] In this study, 26 patients (10.8%) had a history of drug reaction.…”
Section: Discussionmentioning
confidence: 88%
“…A high frequency of seborrheic dermatitis (40%-80%) associated with HIV infection was reported before the use of highly active ART [ 26 ]. However, studies conducted in the ART era in China, India, and the United States have reported low prevalence rates of seborrheic dermatitis [ 9 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%